Pengaruh Nutrisi dalam Pengelolaan Reproduksi Ternak (Studi Literatur) - Yendraliza Yendraliza (Kutubkhanah, 2013)
Nutrients are needed by livestock to maintain the viability of the animal itself. Completeness of nutrients pregnancy, child birth weight, weaning weight and keep the child after the parent state when lactation. While the male animals, completeness nutrients in animal feed can maintain the quality of sperm produced. The food is reasonably necessary for the normal functioning endoktrin. Levels of food affect the synthesis and release of hormones from endoktrin. Growth and development of the reproductive organs of cattle is inhibited by lack of food regardless of whether because of low levels of energy, protein, minerals or vitamins. Therefore it is necessary to maintain forage nutritional completeness in this case will help the management of livestock reproduction. Reproduction disrupted livestock and poultry farms will harm the survival of the animal itself. This paper is a contribution of ideas and a review of several studies on the role of nutrition in animal reproduction.